1996
DOI: 10.3354/meps142135
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biological factors influencing mussel (Mytilus trossulus, M. edulis) settlement on a wave-exposed rocky shore

Abstract: Physical and biological factors influencing mussel(Mytilus trossulus, M. edulis) settlement on a wave-exposed rocky shore Heather L. Hunt*, Robert E. ScheiblingDepartment of Biology, Dalhousie University, Halifax, Nova Scotia, Canada B3H 451ABSTRACT: Settlement rates of mussels Mytjlus trossulus and M, edulis on artificial collectors (aquar~um filter wool) and natural substrata were measured in tidepools and on emergent rock in recently ice-scoured and non-scoured regions of a rocky shore near Halifax, Nova Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 25 publications
5
65
1
4
Order By: Relevance
“…Recruitment of Balanus eburneus was five times higher than that naturally existing in the area when the current intensity suffered a twofold increase. Hunt and Scheibling (1996) observed the settlement rate of Mytilus edulis and M. trossolus in natural and artificial substrates in a rocky shore close to Halifax, Nova Scotia. Recruitment of mytilids was higher in substrates which were submitted to higher current intensity.…”
Section: Effect Of Focus In Relation To Different Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment of Balanus eburneus was five times higher than that naturally existing in the area when the current intensity suffered a twofold increase. Hunt and Scheibling (1996) observed the settlement rate of Mytilus edulis and M. trossolus in natural and artificial substrates in a rocky shore close to Halifax, Nova Scotia. Recruitment of mytilids was higher in substrates which were submitted to higher current intensity.…”
Section: Effect Of Focus In Relation To Different Directionsmentioning
confidence: 99%
“…Different studies have established that larval settlement is affected by current velocity, there existing a critical range for the effectiveness of this event. Although, recently, no study could be found referring to processes involving teredinids, some investigations have focused on the importance of currents to other marine invertebrates (Hunt & Scheibling, 1996, * Author for correspondence on the recruitment of Mytilus trossolus and M. edulis; Manuel et al, 1996, on the migration of Placopecten magellanicus; and Judge & Craig, 1997, on the recruitment of Balanus eburneus). Besides the action of water currents, teredinids may guarantee their long distance dispersion through the infestation of wooden craft hulls or driftwood.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the limit varies substantially among microsites, and an index of local topography was found to predict little of this variation. Thus, caution must be exercised in any attempt to relate observed variations in ocean ''waviness'' to the corresponding rates of microsite disturbance in intertidal communities.Rocky intertidal invertebrates and algae live in a world of extreme environmental severity, and the risk of damage or dislodgment from wave-generated forces is thought to be among the most important determinants of survival in this habitat (e.g., Dayton 1971; Levin and Paine 1974;Koehl 1979; Paine 1979; Paine and Levin 1981;Sousa 1984;Denny 1987Denny , 1988Carrington 1990Carrington , 2002Bertness et al 1991;Hunt and Scheibling 1996;Blanchette 1997). Quantifying the hydrodynamic forces acting on organisms, and how they vary in space and in time, is therefore key to understanding the evolutionary and ecological consequences of morphological design and the subsequent effects of wave-driven forces on the dynamics of intertidal ecosystems (Denny 1988;Koehl 1996;Denny and Wethey 2001;Carrington 2002).…”
mentioning
confidence: 99%
“…Spatial variation in size specific reproductive output could also have important consequences for recruitment as has been described for P. canaliculus and M. californianus (Alfaro et al, 2003;Phillips, 2007). Settlement occurs at low intensities throughout the year and intense settlement occurs during post monsoon (Kuriakose et al, 1984;Hunt and Scheibling, 1996).…”
Section: Discussionmentioning
confidence: 99%